Environmental Management Accounting with Material Flow Cost Accounting: Strategy of Environmental Management in Small and Medium-sized Enterprises Production Activities - Ahmad Maulana Syarif; Novita Novita (Universitas Trisakti, 2018)
The purpose of this research is to analyze activities of related environmental costs that occur and how to manage the use of raw materials and energy in the production process. Research methods used are observation, interview, and documentation. While methods of analysis research data using qualitative descriptive analysis i.e., describing object examined through data collected to produce a generally accepted conclusion. Based on data retrieved explains that activities related to environmental management in the tofu production process has not been made optimally. This impact on the cost of environmental management has not been presented in environmental quality cost report which is divided into four types, namely prevention cost, detection cost, internal failure cost, and external failure cost. The results of the analysis in this research obtained information that raw material costs into positive output (product) of 88,74% and negative output (material losses) of 11,26%. This environmental quality cost report that is used as consideration in management decisions related to waste management as well as increased production practices related use of raw materials and energy in the production process as an effort to reduce material loss and minimize negative impact to the environment.